Cytomegalovirus hepatitis in a 2-month-old infant: a case report - Panez-Gallardo, Jhoana Katherine (2021)
Congenital cytomegalovirus infection is a cause of neonatal infection that can be asymptomatic; however, its complications are possible in some organs such as the nervous system and the liver. We report a case of a 2-month-old female infant with cytomegalovirus hepatitis characterized by abdominal distention, cholestasis, irritability, and poor breastfeeding. In the tests, liver involvement, periventricular microcalcifications, and sensorineural hearing loss were found. The diagnosis was determined by serum antibodies, confirmed with viral load in blood, urine, and liver tissue. Treatment with ganciclovir, vitamin K, and ursodeoxycholic acid was administered with adequate evolution. Cytomegalovirus hepatitis is a complication that may be associated with the involvement of other organs. Antiviral treatment for liver involvement is still controversial; however, it is recommended in children under one month of age if it is associated with neurological damage.